EDUCATIONAL ACTIVITIES BY NURSES IN SCHOOLS: CONTRIBUTIONS TO SYPHILIS PREVENTION AND THE PROMOTION OF SEXUAL HEALTH AMONG ADOLESCENTS - Mikaella Paula Soares de Freitas; Joyce Lara de Lima Mendes; Berenice Moreira; Camila Antunez Villagran; Paula Cristina de Oliveira Pimenta; Mariana Duarte de Castro Giovannetti (Artefactum - revista de estudos interdisciplinares, 2026)
This integrative review aimed to analyze educational actions performed by nurses in school settings and their contributions to syphilis prevention and sexual health promotion among adolescents. The study was conducted through national and international databases (PubMed, Scopus, CINAHL, LILACS, and SciELO), covering publications from 2017 to 2025. A total of 11 studies were included, focusing on educational interventions led by nurses in school or community environments. Findings showed that the active participation of nurses in health education increased adolescents’ knowledge about STIs, improved condom use and testing behaviors, and reduced stigma while fostering open communication between students, families, and schools. Active learning methodologies, school–primary care integration, and family engagement were identified as key factors for the effectiveness of interventions. However, challenges remain, such as the lack of quantitative research and limited pedagogical training for nursing professionals. It is concluded that nurses play an essential role in promoting adolescent sexual and reproductive health, contributing to the consolidation of Health Promotion principles and the Brazilian School Health Program (PSE) guidelines.